Time to Go Our Separate Ways: Opposite Effects of Study Duration on Priming and Recognition Reveal Distinct Neural Substrates - Voss, Joel; Gonsalves, Brian (Frontiers in Human Neuroscience, 2010)
Amnesic patients have difficulties recognizing when stimuli are repeated, even though their responses to stimuli can change as a function of repetition in indirect tests of memory—a pattern known as priming without recognition. Likewise, experimental manipulations can impair recognition in healthy individuals while leaving priming relatively unaffected, and priming and recognition have been associated with distinct neural correlates in these circumstances. Does this evidence necessarily indicate that priming and recognition rely on distinct brain systems? An alternative explanation is that recognition is merely more sensitive to amnestic insults and experimental manipulations than is priming, and that both priming and recognition are produced by a single brain system. If so, then experimental manipulations would tend to drive priming and recognition in the same direction, albeit to a greater extent for one versus the other in some circumstances. We found evidence to the contrary—that manipulating study duration has opposite effects on priming versus recognition. Studying objects for one-quarter second led to worse recognition than studying objects for two seconds, whereas the opposite was true for priming (greater for one-quarter-second study than two-second study). Furthermore, distinct electrophysiological repetition effects were associated with priming versus recognition. We therefore conclude that study duration had opposite effects on priming and recognition, and on the engagement of implicit versus explicit memory systems. These findings call into question single-process accounts of priming and recognition, and substantiate previous behavioral, neuropsychological, and neuroimaging dissociations between implicit and explicit memory.